ANALISIS KEUNTUNGAN PETANI KOPI (Coffea SP) BERDASARKAN DIVERSIFIKASI USAHATANI DI DESA GALANG TINGGI KECAMATAN MEKAKAU ILIR (JASEP, 2021)
The diversification discussed is related to the diversity of farmers' income sources, which is essentially a diterminant of agricultural diversity or called diversification of farms. One of the selected plantation commodities is coffee, because coffee is one of the plantation products that have high economic value. Galang Tinggi is the village that the majority of its work as the largest coffee farmers compared with the villages in mekakau ilir district, coffee cultivated in Galang Tinggi Village is Robusta coffee varieties where coffee is the main source of income for farmers, but the coffee in the farm the community is so old that the coffee production has been reduced to meet the needs of the family then the coffee farmers do other work than coffee ie rice and pepper farming, or better known as the diversification of farming (coffee-rice and coffee-pepper) This study aims to analyze income and analyze the profit using R/C ratio on diversification of farmer I and farming diversification II, The result of analysis shows the average of farmer earnings in the first farming diversification of Rp. 49,584,485 / Kg / Ha / yr. on diversification of farming II Rp.50,380,235 / Kg / ha / yr. And result of analysis of R / C ratio value that ratio of total revenue with total expenditure cost used to see farm profit in Galang Tinggi Village Mekakau Ilir Subdistrict. shows the results of diversification of farming I of 8.53 rupiah, and on diversification II 9 rupiah farming so that farmers who diversify farms I and II is said to be profitableKeywords: Diversification, Farmers, Income, Profit